Third trimester Doppler ultrasound as prediction of obstetric outcome in high-risk pregnancy, Gujarat, India - Ghosh, Runoo; Oza, Hina; Meel, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Doppler ultrasound has emerged as beneficial tool in the assessment of the fetal and placental circulation and in the prediction of adverse pregnancy outcome. Umbilical artery Doppler has proved helpful to supervise the growth restricted fetuses and compromised vasculature as in hypertensive disorders high risk pregnancies. Objective of present study was to investigate the association between third-trimester uterine artery Doppler assessment and adverse obstetric outcome. Methods: This prospective study was done among 110 high risk pregnancies. Vessel like uterine artery, umbilical artery, middle cerebral artery and ductus venosus were studied in present study. Indices calculated: Peak systolic velocity, End diastolic velocity, Mean velocity, Systolic/diastolic ratio, Pulsatility index (PI) and resistance index (RI) of middle cerebral artery (MCA), Ductus venosus S/A ratio. Results: bilateral notch was present statistically significant (p<0.05) in 18.1% and absent in 28.2% among cases of adverse perinatal outcome. UA S/D ratio was >3 in 22.7% and <3 in 11.8% among cases of adverse perinatal outcome and findings were statistically significant (p<0.05). End diastolic velocity was reduced in statistically significant (p<0.05) in 9.1% and normal in 20.1% among cases of adverse perinatal outcome. MCA PI was <lower limit statistically significant (p<0.05) in 24.5% and >lower limit in 18.2% among cases of adverse perinatal outcome. MCA PI/UA PI ratio was <1 statistically significant (p<0.05) in 25.5% and absent in 17.3% among cases of adverse perinatal outcome. Conclusions: Increase in UA PI and decrease in MCA PI are early marker for detection of fetal compromise. Ratio of indices between MCA PI and UA PI reflects brain sparing effect as well as placental insufficiency and these are more specific in detection of IUGR than individual artery indices.